1994
DOI: 10.1111/j.1365-2141.1994.tb05113.x
|View full text |Cite
|
Sign up to set email alerts
|

The endocytic pathway for H‐ferritin established in live MOLT‐4 cells by laser scanning confocal microscopy

Abstract: We have established the intracellular destination of the putative immunoregulatory protein, human recombinant H (heavy)-ferritin, in the transformed T-cell line MOLT-4, by laser scanning confocal microscopy of live cells. A series of confocal images was collected over a 60 min time course using indirect immunofluorescence of H-ferritin and transferrin, their respective monoclonal antibodies, and fluorescein isothiocyanate (FITC)-labelled IgG. A marked drop in FITC fluorescence after 40 min of H-ferritin intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…Taken together these results indicate that the primary method for ferritin uptake into oligodendrocyte progenitors is by clathrin-dependent, receptor mediated endocytosis. Indeed, our results are consistent with microscopic analyses suggesting ferritin is internalized in Molt 4 cells via an endocytic pathway (Moss et al, 1994) and is associated with clathrin coated vesicles in HeLa cells (Bretscher and Thomson, 1983).…”
Section: Discussionsupporting
confidence: 81%
“…Taken together these results indicate that the primary method for ferritin uptake into oligodendrocyte progenitors is by clathrin-dependent, receptor mediated endocytosis. Indeed, our results are consistent with microscopic analyses suggesting ferritin is internalized in Molt 4 cells via an endocytic pathway (Moss et al, 1994) and is associated with clathrin coated vesicles in HeLa cells (Bretscher and Thomson, 1983).…”
Section: Discussionsupporting
confidence: 81%
“…Our demonstration that TIM-2 binds to H-ferritin is the first identification of a cell surface receptor for ferritin, although the existence of ferritin receptors was postulated previously, based on saturable binding of ferritin to the surface of several cell types, including B and T lymphocytes. Thus, binding of H-ferritin to lymphocytes is increased in mitogen-stimulated cells, and purified H-ferritin forms surface patches on T cells, after which it is endocytosed into lysosomes (23,24,32). Studies using MOLT-4 human T cells indicated that they express a receptor for H-ferritin with an association constant of ‫ف‬ 7 ϫ 10 Ϫ 7 L/mol, and that the receptor is increased on proliferating cells (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that the cell lines that are particularly sensitive to trioxane dimers 14a and 14b all express transferrin. Transferrin is an endogenous protein that transports iron from the circulation into cells. Most cancer cell lines express higher surface cell concentrations of transferrin receptors than normal cells and have higher rates of iron influx 26a.…”
Section: Antitumor Activitiesmentioning
confidence: 99%